SOSIALISASI TENTANG PEMAHAMAN Vaksin Covid-19 DI WILAYAH KELURAHAN JEBRES SOLO - Ariawan, M. Wahyu; Koernia, Lilik Wahidah; Widiyastuti, Asih; Prasetyawan, Fendy (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
The results of a vaccine acceptance survey conducted by the Ministry of Health together with ITAGI (Indonesian Technical Advisory Group on Immunization) with support from UNICEF and WHO in September 2020 showed that the majority of the public (74 percent) already knew about the government's plans to carry out COVID-19 vaccination. As many as 65 percent are willing to be vaccinated, around 27 percent are still hesitant. And only a small percentage or around 8 percent said they refused because they were worried about the safety, effectiveness and halalness of the vaccine. The survey results also show that those who have information about COVID-19 vaccination are more likely to accept COVID-19 vaccination. This shows the importance of ensuring that all people have access to accurate information about handling COVID-19, including about COVID-19 vaccination. (Ministry of Health, 2021) The problem that arises now is that there is a lot of hoax news circulating through social media that is widely spread to the public. So it can lead public opinion to be afraid and not want to be vaccinated. This socialization was held with the theme